EFFECT OF USING IRRIGATION WATER IN DEFFIRENT QUALITIES AND BIO-FERTILIZER IN SOME CHEMICAL PROPERTIES OF CALCAREOUS SOIL - & Al-Joubory, Salman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A pots experiment was conducted at the canopy wood of Agriculture - University of Baghdad (Abu-Ghraib) during summer season of 2014 to study the effect of irrigation water quality and biofertilizer and their interactions on some soil chemical properties and growth of corn. Treatments included three water qualities river water (1.5 ds.m-1 ''Q1''), well water (4.4 ds.m-1 ''Q3'') and mixed water (3.0 ds.m-1 ''Q2'') and two levels of biofertilizer (without inoculation ''B0'' and inoculation with Azotobacter chroococcum, Bacillus megaterium and Pseudomonas fluorescens  ''B1'') applied to clay loam soil, using complete randomization design (CRD) in three replicates. The results of study Soil EC values increased with increasing water salinity giving 5.18, 6.03 and 6.70 ds.m-1 for Q1, Q2 and Q3, respectively. And significantly increased exchange capacity of the cation ions CEC reached 22.20, 23.01 and 24.31 c mole c kg-1 soil for Q1, Q2 and Q3, respectively. Irrigation water salinity also led to a significant increase in soil organic matter content reached 11.06, 12.55 and 13.90 gm.kg-1 soil for Q1, Q2 and Q3, respectively. Biofertilization led to decrease in rates a significant values electrical conductivity (EC) increase exchange capacity of the cation ions CEC and organic matter soil.